Virtual-Build-to-Order as a Mass Customization Order Fulfilment Model - Brabazon, Philip G.; MacCarthy, Bart L. (Sage Publications, 2004)
Virtual-build-to-order (VBTO) is a form of order fulfilment system in which the producer has the ability to search across the entire pipeline of finished stock, products in production and those in the production plan, in order to find the best product for a customer. It is a system design that is attractive to Mass Customizers, such as those in the automotive sector, whose manufacturing lead time exceeds their customers' tolerable waiting times, and for whom the holding of partly-finished stocks at a fixed decoupling point is unattractive or unworkable. This paper describes and develops the operational concepts that underpin VBTO, in particular the concepts of reconfiguration flexibility and customer aversion to waiting. Reconfiguration is the process of changing a product's specification at any point along the order fulfilment pipeline. The extent to which an order fulfilment system is flexible or inflexible reveals itself in the reconfiguration cost curve, of which there are four basic types. The operational features of the generic VBTO system are described and simulation is used to study its behaviour and performance. The concepts of reconfiguration flexibility and floating decoupling point are introduced and discussed.